Analysis of Islamic Education Policy: Philippines Case Study - Imran Rido; Siti Halimah; Husni Mubarok (Institut Agama Islam Hidayatullah Batam, 2022)
This study aims to Analysis Of Islamic Education Policy: Philippines Case Study. This research includes qualitative research. The approach used is pure library research (library research). Data obtained from reading materials obtained by researchers from books, articles contained in print. Data were collected and sorted to fill in the answers to the formulated research questions. The analysis uses a content analysis approach that is adapted to the need to develop historical linkages and the dynamic context of madrasas in the Philippines. The conclusion of this study is that Islam in the Philippines has experienced ups and downs from a religion that was once great marked by the presence of Islamic empires such as Manila, Manguindanau and Sulu to become minority groups caused by colonialism carried out by Spain, America and Japan. Islamic education policies in the Philippines, the Philippine government is trying to include an Islamic education system such as madrasas in the national education system, accommodation for madrasa education in the Philippine education system has begun to progress since the Philippine government adopted DO 51 which includes teaching Arabic and Islamic values ​​in public schools, and testing the standard curriculum or what is often called the Standard Madrasa Curricula (SMC) in private madrasas; The impact of Islamic education policies in the Philippines, namely the Philippine government in developing madrasa education, has learned a lot from the development of madrasas in Indonesia.